Den argumenterande fornuft - Gunnar Skirbekk (Norsk Filosofisk Tidsskrift)
Abstract This paper, on argumentative reason in a modernization-theoretical perspective, is a revised version of a public lecture held at Oslo University College, in memory of Professor Harald Grimen. There are three main points: argumentative reason conceived as self-critical reflection, to be extended to arguments from absurdity – from Apel to Ryle, as it were; argumentative reason conceived as a search for better arguments, ideally with mutual recognition and personal improvement – a meliorist approach; argumentative reason conceived as situated learning-processes, socially and institutionally. In short, a special blend of late-Wittgensteinian praxeology, transcendental-pragmatics and discourse theory, as it is discussed in my writings.